2016
DOI: 10.1186/s40064-016-2229-y
|View full text |Cite
|
Sign up to set email alerts
|

Oolong tea made from tea plants from different locations in Yunnan and Fujian, China showed similar aroma but different taste characteristics

Abstract: Consistent aroma characteristics are important for tea products. However, understanding the formation of tea aroma flavor and correspondingly proposing applicable protocols to control tea quality and consistency remain major challenges. Oolong tea is one of the most popular teas with a distinct flavor. Generally, oolong tea is processed with the leaves of tea trees belonging to different subspecies and grown in significantly different regions. In this study, Yunnan and Fujian oolong teas, green tea, black tea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 28 publications
(29 reference statements)
2
45
0
1
Order By: Relevance
“…Moreover, soluble sugar also increases due to macromolecular substances, such as starch and others hydrolysis to glucose, fructose, sucrose. (Wang et al, 2016). Note that the decrease in catechins and bitter amino acids could effectively reduce the astringency and bitterness of green tea, while the increase in total soluble sugars and sweet amino acids could balance the flavour of tea infusion.…”
Section: (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, soluble sugar also increases due to macromolecular substances, such as starch and others hydrolysis to glucose, fructose, sucrose. (Wang et al, 2016). Note that the decrease in catechins and bitter amino acids could effectively reduce the astringency and bitterness of green tea, while the increase in total soluble sugars and sweet amino acids could balance the flavour of tea infusion.…”
Section: (D)mentioning
confidence: 99%
“…A great number of studies reported that the tea polyphenols, amino acids, soluble sugars and chlorophyll contents decreased in roasting process. Meanwhile, amino acids and soluble sugars involved in Maillard reaction, which formed many roasted flavour compounds and effectively improved the sensory quality of tea (Wan et al, 2000;Wang et al, 2016). Recently, there has been an increase on the study of oolong tea, and most researches focused on the effects of roasting on the aroma of tea.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated hydrocarbons usually make a minor contribution to the tea aroma, whereas unsaturated hydrocarbons are important contributors to the tea aroma [23]. D-limonene is considered an important volatile and is described as having a "lemon-like" aroma.…”
Section: Discussionmentioning
confidence: 99%
“…Water‐soluble sugar (WSS) content was determined by visible spectrophotometer method with anthraquinone on 620 nm (Liang et al, 2005). Contents of GA and catechins, including C, EC, EGC, ECG, and EGCG, were determined by HPLC using an Agilent 1200 Series system with Agilent C 18 Chromatogram column (250 mm × 4.6 mm, 5 μm) (Wang et al, 2016). Caffeine content was determined by Agilent 1200 HPLC equipment using Agilent C 18 Chromatogram column (250 mm × 4.6 mm, 5 μm) with solvent A (100% acetonitrile) and solvent B (0.2% v/v acetic acid–water solution) as mobile phase (Tan et al, 2012).…”
Section: Methodsmentioning
confidence: 99%